Edukasi Dampak Penggunaan Gadget pada Anak di Rumah Baca Rangka Pustaka Kabupaten Aceh Utara - Sari, Dian Vita; Fatmawati, Fatmawati; Junaedy, Junaedy; Ahmady, Dedy (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background Recently, the development of technology is also becoming more advanced. Today's technology is able to bring about a new era where everything becomes fast-paced practicality. The negative impacts of excessive gadget use include gadget addiction, sleep disturbances, eye fatigue, poor posture, impaired close vision, and decreased cognitive abilities. The purpose of this community service is to provide counseling on the impact of gadget use on children at the reading house of the library framework in North Aceh district. Method The implementation of community service is face-to-face, using the counseling method. This activity was carried out on Tuesday, 31 October 2023 at the Rangkang Pustaka Reading House in Nisam village, North Aceh Regency. The counseling was conducted for children aged 7 to 11 years. who are at the elementary school,with a total of 37 participants. The results showed that from a total of 37 children, it was found that 13 already had sufficient understanding of the impact of gadget use, while 24 still did not have knowledge and understanding of the adverse effects that arise from the use of gadgets. In conclusion, gadgets can reduce the ability to think and analyze things, and can have long-term and permanent consequences if not addressed early on. This activity is very helpful for children to become independent and reduce smartphone addiction.